109k views
21 votes
F(x)=3^x-4x^2+6x and g(x)=5x^3+2x^2-3x. What is f(x)-g(x)

1 Answer

6 votes

Answer:

  • -4x³ - 6x² + 9x

Explanation:

Given functions:

  • f(x) = x³ - 4x² + 6x
  • g(x) = 5x³ + 2x² - 3x

f(x) - g(x) is the difference of the above expressions:

  • f(x) - g(x) =
  • x³ - 4x² + 6x - (5x³ + 2x² - 3x ) = ⇒ Substitute
  • x³ - 4x² + 6x - 5x³ - 2x² + 3x = ⇒ Open parenthesis
  • x³(1 - 5) - x²(4 + 2) + x(6 + 3) = ⇒ Combine like terms
  • -4x³ - 6x² + 9x ⇒ Simplify
User Krusty
by
5.0k points